A rare case of schwannoma of maxillary sinus - Dixit, Pawan K; Mishra, Brijesh; Maurya, Malti; Upadhyay, Divya Narain (Indian Journal of Case Reports, 2018)
Schwann cell tumor or schwannomas is the benign nerve sheath tumors, which arise mostly from head and neck region and rarely from the nasal and paranasal sinuses. Of these, very few arise solely from the maxillary sinus. This is a case report of a 25-year-old female patient presenting with painful swelling below the right eye turned out to be a rare case of schwannoma arising solely from the maxillary sinus. Details of clinical history, examination, histopathological finding, radiological finding, treatment, and follow-up have been presented.